Project-Based Learning and Students’ Content Achievement: Second Baccalaureate Students as a Case Study - khamouja, Abdessallam (International Journal of Linguistics and Translation Studies, 2025)
Students’ achievement refers to the extent to which learners have acquired their short or long-term educational goals. Good academic achievements give students the opportunity to enhance the necessary knowledge and practical skills they will need in their future schooling. This pushes teachers to rely on modern teaching methods in their teaching process, such as project-based learning, to make their students successful in their learning. Therefore, the researcher conducted a quasi-experimental research design to find out if there is any significant difference between the means of the experimental and control groups before and after the experiment at the second-year baccalaureate level. Forty students participated in the experiment. They were divided into the experiment and control groups. The experimental group was given a project to conduct, and the control group started studying Unit 4 of the Ticket 2 English Textbook. The findings indicate that there is a significant difference between the means of the experimental and control groups after the experiment. Consequently, it is suggested that teachers should adopt project-based learning in their teaching process to help students learn the subject content successfully.